Prognostic Significance of Tumor-Infiltrating Natural Killer Cells in Solid Tumors: A Systematic Review and Meta-Analysis - Zhang, Shuo; Liu, Weijian; Hu, Binwu; Wang, Peng; Lv, Xiao; Chen, Songfeng; Shao, Zengwu (Frontiers in Immunology, 2020)
Background: Tumor-infiltrating natural killer (NK) cells (TINKs) were crucial immune cells in tumor defense, which might be related to tumor prognosis. Nevertheless, the results were discrepant among different studies. The present meta-analysis was performed to comprehensively assess the prognostic value of NK cell markers in solid tumor tissues. Methods: PubMed, Web of Science, and EMBASE were searched to identify original researches reporting the prognostic significance of TINKs in solid tumors. NK cell markers CD56, CD57, NKp30, and NKp46 were included in the analysis. The hazard ratios (HRs) and 95% confidence intervals (CIs) of pooled overall survival (OS), disease-free survival (DFS), metastasis-free survival (MFS), progression-free survival (PFS) and recurrence-free survival (RFS) were calculated by STATA software 14.0 to assess the prognostic significance. Results: Of the fifty-six included researches, there were 18 studies on CD56, 31 studies on CD57, 1 study on NKp30 and 7 studies on NKp46. High levels of CD56, CD57, NKp30 and NKp46 were significantly correlated with better OS of patients with solid malignancies (HR=0.473, 95%CI: 0.315-0.710, p<0.001; HR=0.484, 95%CI: 0.380-0.616, p<0.001; HR=0.34, 95%CI: 0.14-0.80, p =0.014; HR=0.622, 95%CI: 0.470-0.821, p<0.001, respectively). Our results also revealed that CD56, CD57 and NKp46 could act as independent prognostic predictors for favorable OS (HR=0.372, 95%CI: 0.261-0.531, p<0.001; HR=0.525, 95%CI: 0.346-0.797, p=0.003; HR=0.559, 95%CI: 0.385-0.812, p=0.002, respectively). Conclusions: Our results indicated that high-degree NK cell markers in solid tumor tissues could predict favorable prognosis of solid tumor patients.